Comments on "Entropy optimization and heat transfer modeling for Lorentz forces effect on solidification of NEPCM". (November 2020) - Awad, M.M.
Abstract: These comments show that the entropy generation units due to fluid friction (Sgen, f ) and magnetic field (Sgen, m ) are kg m −1 s −3 K −2 . Hence, the total entropy generation (Sgen, total ) equation is wrong. Proper correct expressions of Sgen, f and Sgen, m are given.